PEREMPUAN DALAM NOVEL DESTROY,SHE SAID KARYA MARGUERITE DURAS : ANALISIS FEMINISME KEKUASAAN NAOMI WOLF - Muhammad Fadli Muslimin (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2019)
This research raises the issue of women which focuses on women's efforts to dominate amidst male domination. Qualitative research with descriptive methods is utilized, along with the use of the theory of feminism Naomi Wolf's power as a knife of analysis is used to address issues regarding women's power over women and their functions. The purpose of this research is to reveal the power and function of women's power in the novel Destroy, She Said by Merguerite Duras. The results of this study indicate that women have the power gained from self-charm, assertiveness, obstinacy. This power is used by women to dominate men, but the dominance that is born does not make women superior, but rather places women as equals to men.